Rituximab in the treatment of multiple sclerosis in the Hospital District of Southwest Finland - Laura Airas; Marjo Nylund; Iina Mannonen; Markus Matilainen; Marcus Sucksdorff; Eero Rissanen (My University, 2026)
Background
There are already numerous B-cell depleting monoclonal anti-CD20 antibodies which have been used to reduce the inflammatory burden associated with multiple sclerosis (MS). We describe here our experience of treating MS-patients with B-cell depleting rituximab.
Patients and methods
All MS-patients (n = 72) who had received rituximab treatment for at least six months by January 2019 were identified from the patient charts at the Turku University Hospital. Information about MS disease subtype, disease severity, MR-imaging outcomes and B-cell counts were collected from the charts.
Results
Rituximab was well received and well tolerated by the patients. There were no serious infusion-related side effects. The most serious adverse event that led to treatment discontinuation was neutropenia. After rituximab initiation the annual number of relapses was decreased in the relapsing remitting and secondary progressive MS groups and the mean number of gadolinium-enhancing lesions was decreased in relapsing remitting MS. Our study confirms the usability of rituximab treatment for MS in the Finnish health care environment.
Conclusions
Off-label rituximab-treatment can be successfully used to reduce MS disease burden for the benefit of MS patients.